Inkjet Printing of Conductive Inks with High Lateral Resolution on Omniphobic "RF Paper" for Paper‐Based Electronics and MEMS. (30th May 2014) - Lessing, Joshua; Glavan, Ana C.; Walker, S. Brett; Keplinger, Christoph; Lewis, Jennifer A.; Whitesides, George M.
<x xml:space="preserve">Abstract</x> The use of omniphobic "fluoroalkylated paper" as a substrate for inkjet printing of aqueous inks that are the precursors of electrically conductive patterns is described. By controlling the surface chemistry of the paper, it is possible to print high resolution, conductive patterns that remain conductive after folding and exposure to common solvents. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>